2023
DOI: 10.2147/jir.s421021
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Lung Cancer Inflammation Index for Predicting Prognostic Risk for Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Xinchen Wang,
Chen Wei,
Wenjun Fan
et al.

Abstract: Purpose The decreased advanced lung cancer inflammation index (ALI), defined as body mass index (BMI) * albumin (Alb)/neutrophil-to-lymphocyte ratio (NLR), is an independent prognostic risk factor for overall survival in gastric, lung, and colorectal cancers. This study aimed to investigate the value of ALI in predicting the risk of major adverse cardiovascular events (MACEs) in patients with acute coronary syndrome (ACS). Patients and Methods A total of 1624 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Recently, scholars have identified ALI < 334.96 to be an independent prognosis risk factor for acute coronary syndrome patients who underwent percutaneous coronary intervention. 16 This study suggested that ALI could serve as a novel biomarker in therapeutic settings. Despite the recognized importance of inflammation and nutrition in the context of CAP, research regarding the predictive value of ALI in CAP patients is lacking.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, scholars have identified ALI < 334.96 to be an independent prognosis risk factor for acute coronary syndrome patients who underwent percutaneous coronary intervention. 16 This study suggested that ALI could serve as a novel biomarker in therapeutic settings. Despite the recognized importance of inflammation and nutrition in the context of CAP, research regarding the predictive value of ALI in CAP patients is lacking.…”
Section: Discussionmentioning
confidence: 85%
“…This index can simultaneously re ect the nutritional and in ammatory status of patients [14]. he correlation between a lower ALI and poorer prognosis has been established in various cancers and in ammatory diseases [15][16][17][18][19][20][21]. Nonetheless, research on the clinical signi cance of the ALI in bronchiectasis patients remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…The Advanced Lung Cancer In ammation Index (ALI), which integrates BMI, the serum ALB concentration, and the neutrophil-to-lymphocyte ratio (NLR), was initially developed by Jafri et al to evaluate the prognosis of patients with metastatic non-small cell lung cancer (NSCLC) [14]. Subsequent studies have demonstrated that the ALI is effective in predicting the outcomes of various cancers, including hepatocellular carcinoma, esophageal squamous cell carcinoma, gastric cancer, colorectal cancer, and even benign conditions such as hypertension, acute coronary syndrome, and diabetes mellitus [15][16][17][18][19][20][21]. Additionally, the ALI has been utilized as a predictor of postoperative complications in colon cancer patients [22].…”
Section: Introductionmentioning
confidence: 99%